Optimalisasi Penggunaan Media Sosial Sebagai Sarana Pembelajaran Era Digital Di Sekolah MA Darul Qalam Bengkulu Tengah (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2025)
In today's digital era, social media has become an effective platform to support the teaching and learning process. Unfortunately, the many benefits of learning media through social media also do not rule out the possibility that it will have a negative effect on those who use it carelessly and unwisely. The Team of Lecturers and Students of the FKIP Dehasen University of Bengkulu in community service in Lubuk Unen Village, Merigi Kelindang District, Central Bengkulu Regency which was carried out on November 11, 2024, provided assistance for class XII students at MA Darul Qalam Central Bengkulu through socialization and strengthening motivation related to optimizing the use of social media as a learning tool in the digital era. In this assistance, students were given knowledge about the importance of digital literacy and the use of social media as a learning tool along with training on how to use social media so that they can increase interaction and collaboration in learning. The results of this activity showed an increase in students' interest, understanding and skills in using technology as a learning tool. The success of this activity was marked by their enthusiasm during the activity, namely being active and providing positive responses to the material presented by the community service team. Grade XII students at MA Darul Qalam can follow a series of activities well and understand the benefits of social media as a learning tool in the digital era. The use of social media is expected to enrich the learning experience to equip students to face the challenges of the digital era.
Keywords: Optimization; Social Media; Learning Tools; Digital Era